2020
DOI: 10.3389/fonc.2020.01474
|View full text |Cite
|
Sign up to set email alerts
|

Increased ABCC4 Expression Induced by ERRα Leads to Docetaxel Resistance via Efflux of Docetaxel in Prostate Cancer

Abstract: Docetaxel is a major treatment for advanced prostate cancer (PCa); however, its resistance compromises clinical effectiveness. Estrogen receptor-related receptor alpha (ERRα) belongs to an orphan nuclear receptor superfamily and was recently found to be closely involved in cancer. In the present study, we found that ERRα was involved in docetaxel resistance in PCa. Overexpression of ERRα conferred docetaxel resistance in PCa cell lines, and cells with ERRα downregulation were more sensitive to docetaxel. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…ERRα also mediated chemoresistance of osteosarcoma cells by regulating ABCB1 [17]. Similarly, Huang found that ERRαinduced increased expression of ABCC4 could promote docetaxel e ux and lead to the development of drug resistance in prostate cancer [29]. Collectively, these studies indicate that ERRα plays a critical role in tumor-acquired drug resistance and may serve as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 83%
“…ERRα also mediated chemoresistance of osteosarcoma cells by regulating ABCB1 [17]. Similarly, Huang found that ERRαinduced increased expression of ABCC4 could promote docetaxel e ux and lead to the development of drug resistance in prostate cancer [29]. Collectively, these studies indicate that ERRα plays a critical role in tumor-acquired drug resistance and may serve as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 83%
“…ERRα also mediated chemoresistance of osteosarcoma cells by regulating ABCB1 [20]. Similarly, Huang found that ERRαinduced increased expression of ABCC4 could promote docetaxel e ux and lead to the development of drug resistance in prostate cancer [34]. Collectively, these studies indicate that ERRα plays a critical role in tumor-acquired drug resistance and may serve as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 83%
“…ABCC4 is widely expressed in various tissues [50][51][52], and can actively transport a series of organic anions to extracellular, so most of the functional studies on ABCC4 are focused on its effect on cancer chemotherapy [53]. A large number of studies have found that ABCC4 is related to drug resistance in prostate cancer, breast cancer, colorectal cancer, pancreatic cancer, lung cancer and other cancers [54][55][56]. Nonetheless, other studies have uncovered that low expression of ABCC4 can lead to the accumulation of cAMP in cells, which increases the invasiveness and migration of cancer cells [57].…”
Section: Discussionmentioning
confidence: 99%